DEVELOPMENT AND RESEARCH OF TECHNOLOGICAL PARAMETERS OF A NEW TYPE OF LOCAL TEXTILES FABRIC (American Journal of Interdisciplinary Research and Development, 2024)
This article talks about the production and research of technological parameters of a new type of linen fabric from local raw materials, the introduction of innovative ideas and the application of scientific innovations in the field.